Evaluasi Daya Hasil Cabai Hibrida dan Daya Adaptasinya di Empat Lokasi dalam Dua Tahun - Muhamad Syukur; Sriani Sujiprihati; Rahmi Yunianti; Darmawan Asta Kusumah (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2010)
The aim of the experiment was to study the performance of yield components of  eight pepper hybrids and their adaptation at four locations in two years (2008 and 2009). The experimental design used was Randomized Complete Block Design (RCBD), three replications as a block was nested in the location. Plant materials were eight hybrids (IPB CH1, IPB CH2, IPB CH3, IPB CH25, and four commercial hybrids were Adipati, Biola, Gada, and Hot Beauty). The IPB CH3 hybrid produced higher fruit width, fruit length, fruit weight, fruit flesh density and yield per plant compared to commercial hybrids. Days to flowering and days to harvesting of IPB CH3 was earlier than that of Hot Beauty. The performance of yield characters in Boyolali, Rembang and Subang was better than that in Bogor. The IPB CH3 hybrid was specifically adapted to Subang and Rembang, while IPB CH1, IPB CH2, IPB CH25 were suitable for Boyolali.   Keywords: fruit, yield components, genotype x location interaction, Capsicum annuum L.